BUILDING CHILDREN CHARACTER IN ISLAMIC EDUCATION - Muhammad Fuad Ikhwansyah; Rahman Tanjung; Kurniawan Arif Maspul; Firmansyah Firmanysah; Fina Amalia (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Character education is education that focuses on developing good personalities in children. Character education aims to form good personalities who are responsible, have good morals, are moral, tolerant, and other good personalities. The aim of the research is to find out how to shape children's character with an Islamic perspective in order to produce a generation with good moral character. The research method used in this writing is library research where the author carries out stages relating to methods of collecting, reading and recording and processing library data as research material. The results obtained from this research are that Islamic education has quite an influence on the formation of children's character. When children receive sufficient provision regarding the teachings they believe in, the child will grow and develop into a person who believes and is devoted to Allah SWT, has noble character which includes morals, ethics, spiritual character or experience of values and understanding of religious values. actualized in everyday life.